Penerapan Model Think Pair Share Berbantuan Wordwall untuk Meningkatkan Keterampilan Membaca Nyaring Kelas V - Zulfaiza, Sherlita; Purwati, Panca Dewi (YASIN, 2025)
This study is motivated by the low oral reading skills of elementary school students and the limited innovation in Indonesian language learning that integrates cooperative models with digital and interactive media. It aims to analyze the effectiveness of implementing the Think Pair Share (TPS) model supported by Word Wall media and interactive books in improving oral reading skills among fifth-grade students at SD Mangkang Wetan 02. The study employed a mixed methods design with quantitative and qualitative approaches. The participants were 28 fifth-grade students selected using purposive sampling. Data were collected through observation, oral reading tests, and interviews, and were analyzed using paired t-tests and thematic analysis. The results show a significant improvement in oral reading skills, with the mean score increasing from 63.25 to 84.60 (p < 0.05). Improvements were observed in fluency, intonation, and pronunciation accuracy, accompanied by increased student self-confidence. The findings indicate that the implementation of the TPS model assisted by Word Wall media and interactive books is effective in enhancing oral reading skills and fostering a collaborative and enjoyable learning environment. This study is expected to contribute to the development of Indonesian language literacy instruction in elementary schools.